Students' perception towards the newly implemented Goods and Services Tax (GST) in Malaysia - Ishak, Nor Iza; Othman, Muhammad Hanif; Omar, Muhamad Fuzi (International Journal of Contemporary Applied Sciences (IJCAS), 2015)
The purpose of this paper is to investigate the students’ perception towards the newly implemented Goods and Service Tax (GST) that has been implemented in Malaysia starting from April 1, 2015. The students’ perception is measured through satisfaction analysis. Sets of questionnaire has been designed and distributed to 242 students at International Islamic University Malaysia (IIUM) and later analyzed using SPSS. The result shows that majority of the students disagree with the methods taken to implement the GST.